Gold nanoparticles decorated on single layer graphene applied for electrochemical ultrasensitive glucose biosensor - Yuan, Yawen; Wang, Yishi; Wang, Hua; Hou, Shifeng (Journal of electroanalytical chemistry (Lausanne, Switzerland), 2019)
A glucose biosensor was fabricated by glucose oxidase (GOD) immobilized on gold nanoparticles decorated on single layer graphene (Au/SLG) modified glassy carbon electrode, with 6-(ferrocenyl)hexanethiol (Fc–C6H12–SH) as electron transfer medium (GOD/Fc/Au/SLG/GCE). The free-standing Au/SLG was obtained by sputtered gold nanoparticles on chemical vapor deposition (CVD)-generated monolayer graphene. This process avoids complicated polymer-transfer processes of graphene and affords AuNPs with good dispersion and clean surface promoting immobilization of GOD. Since the clean surface and lower background current of free-polymer-transferred CVD-generated graphene, the ductility monolayer graphene is suit for ultrasensitive detection of low concentration of glucose. Synergy with electron mediator facilitates electron transfer process, the sensor has enhanced electrochemical performance with the detection limit of 0.1 nM (S/N = 3) and good selectivity. The sensor was further studied for real perspiration test with attractive feasibility, which has potential application in perspiration-based wearable glucose detection. A glucose biosensor was fabricated by glucose oxidase (GOD) immobilized on gold nanoparticles decorated free-polymer transfer CVD-generated single layer graphene (Au/SLG) modified glassy carbon electrode, with 6-(ferrocenyl)hexanethiol (Fc–C6H12–SH) as electron transfer medium. [Display omitted] •Novel glucose biosensor was constructed by CVD-generated graphene supported AuNPs modified GCE.•AuNPs with clean surface and good dispersion on graphene facilitate the immobilization of GOD and electron transfer.•Low background current enhance sensitivity with ultralow detection limit of 0.1 nM (S/N = 3).•One-step sputtering AuNPs and polymer-free transfer graphene have potential value in electrochemical filed.